A rare anterior mediastinal mass: Giant Thymolipoma (Annals of Medical Research, 2021)
A 29-year-old male patient was admitted to the emergency with complaints of fever, nausea, vomiting and abdominal pain. Computed Tomography (CT), demonstrates an enlarged appendix vermiformis with mucosal enhancement represent inflammation. The patient was diagnosed with appendicitis and underwent surgery. In addition, while examining the abdominal CT, a mass was detected incidentally in the supradiaphragmatic area, which was partially included in the images, and contrast-enhanced thoracic CT was applied. We aim to present the patient diagnosed with thymolipoma according to thoracic CT result. Thymolipoma is a rare condition and resection of the lesion and thymus should be performed with video thoracoscopic surgery.